A novel SUMO1-specific interacting motif in dipeptidyl peptidase 9 (DPP9) that Is important for enzymatic regulation - Pilla, Esther; Melchior, Frauke (The journal of biological chemistry, 2012)
Sumoylation affects many cellular processes by regulating the interactions of modified targets with downstream effectors. Here we identified the cytosolic dipeptidyl peptidase 9 (DPP9) as a SUMO1 interacting protein. Surprisingly, DPP9 binds to SUMO1 independent of the well known SUMO interacting motif, but instead interacts with a loop involving Glu67 of SUMO1. Intriguingly, DPP9 selectively associates with SUMO1 and not SUMO2, due to a more positive charge in the SUMO1-loop. We mapped the SUMO-binding site of DPP9 to an extended arm structure, predicted to directly flank the substrate entry site. Importantly, whereas mutants in the SUMO1-binding arm are less active compared with wild-type DPP9, SUMO1 stimulates DPP9 activity. Consistent with this, silencing of SUMO1 leads to a reduced cytosolic prolyl-peptidase activity. Taken together, these results suggest that SUMO1, or more likely, a sumoylated protein, acts as an allosteric regulator of DPP9.